Flowering Times of Wild Arabidopsis Accessions From Across Norway Correlate With Expression Levels of FT, CO, and FLC Genes - Kinmonth-Schultz, Hannah; Lewandowska-Sabat, Anna; Imaizumi, Takato; Ward, Joy K.; Rognli, Odd Arne; Fjellheim, Siri (Frontiers in Plant Science, 2021)
• Temperate species often require or flower most rapidly in long summer daylengths (photoperiods) or after prolonged cold temperatures (vernalization). Yet, even within species, plants vary in the degree of responsiveness to these cues. In Arabidopsis thaliana, CONSTANS (CO) and FLOWERING LOCUS C (FLC) genes are key to photoperiod and vernalization perception and antagonistically regulate FLOWERING LOCUS T (FT) to influence when plants flower. How these genes vary in their interactions among wild accessions with different flowering behaviors and adapted to different microclimates is still an open question, yet this knowledge could improve our ability to predict plant responses in variable natural conditions. • To assess the relationships among these genes and to flowering time, we exposed ten winter-annual Arabidopsis accessions from throughout Norway, ranging from early to late flowering, along with two summer-annual accessions to 14 weeks of vernalization and either 8- or 19-hr photoperiods to mimic Norwegian climate conditions, then assessed gene expression levels three, five, and eight days post vernalization. • CO and FLC explained both FT levels and flowering time (days) but not rosette leaf number at flowering. The correlation between FT and flowering time increased over time. Although vernalization suppresses FLC, FLC was high in the late-flowering accessions. Across accessions, FT was expressed only at low FLC levels and did not respond to CO in the late-flowering accessions. • We propose that FT may only be expressed below a threshold value of FLC and demonstrate that these three genes correlate to flowering times across genetically distinct accessions of Arabidopsis.